Desexualisation in later life : the limits of sex and intimacy (Sex and Intimacy in Later Life., 2021)
Despite evidence of a more sexually active 'third age', ageing and later life (50+) are still commonly represented as a process of desexualisation. Challenging this assumption and ageist stereotypes, this interdisciplinary volume investigates the experiential and theoretical landscapes of older people's sexual intimacies, practices and pleasures. Contributors explore the impact of desexualisation in various contexts and across different identities, orientations, relationships and practices. This enlightening text, reflecting international scholarship, considers how we can distinguish the real challenges faced by older people from the prejudices imposed on them.